A high-toughness, moisture-resistant, low-halogen epoxy resin composition
Patent Information
- Application Number
- CN202611469293.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0008]本发明的目的是解决现有技术中存在的缺点,而提出的一种在维持高刚性与高耐热性的前提下,同时具备优异韧性与低吸水率的高韧性耐湿热低卤素环氧树脂组合物,解决了现有环氧树脂体系存在的脆性大抗冲击性差、耐湿热性不足易翘曲、添加橡胶增韧会降低耐热性和刚性且易产生外观缺陷的技术问题
[0030](1)卓越的抗冲击与防爆裂性能:本发明采用了具有本征增韧结构的联苯芳烷基或萘酚骨架硬化剂,制备所得的环氧树脂组合物固化后具有极高的缺口冲击强度,使用本发明的复合材料制成的电子产品外壳,在落球冲击测试或整机跌落测试中的通过率将显著提高,能够有效防止因意外跌落导致的背板开裂或爆裂。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, specifically to a high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition. Background Technology
[0002] In recent years, as consumer electronics products have developed towards being "lighter, thinner, shorter, smaller" and "higher quality," traditional unibody metal casings (such as aluminum-magnesium alloys and stainless steel) have been gradually replaced by fiber-reinforced polymer (FRP) composites due to their heavy weight, high processing costs, and signal shielding issues. Among them, carbon fiber reinforced polymer (CFRP) composites have become the preferred material for structural components such as back panels of high-end laptops, tablets, and mobile phones due to their extremely high specific strength, specific stiffness, and unique appearance.
[0003] In carbon fiber composites, epoxy resin is the most commonly used matrix resin due to its excellent mechanical properties, heat resistance, and good interfacial bonding ability with carbon fibers. However, existing epoxy resin systems still face a series of difficult-to-balance technical contradictions when directly applied to thin-walled backplanes of electronic products, specifically in the following aspects:
[0004] (1) High brittleness and poor impact resistance: In order to achieve high rigidity to support thin-walled structures, traditional formulations often use common phenolic resins with high cross-linking density as hardeners. This results in extremely brittle materials that are prone to cracking or brittle fracture in drop or bending tests.
[0005] (2) Insufficient resistance to damp heat leads to warping: Electronic product back panels have extremely high requirements for dimensional stability. If the resin system has a high water absorption rate (such as using DICY or ordinary resin), it will generate internal stress after absorbing moisture in a humid and hot environment, which will cause the back panel to warp and deform, affecting the assembly accuracy and appearance.
[0006] (3) Appearance defects: Traditional toughening methods often involve adding rubber elastomers. While this can increase toughness, it can significantly reduce heat resistance (Tg) and rigidity, and can easily lead to flow lines or fogging on the appearance, making it unsuitable for appearance parts.
[0007] Therefore, there is an urgent need for an epoxy resin composition that can maintain high rigidity and high heat resistance while also possessing excellent toughness and low water absorption, in order to solve the problems existing in the prior art. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of the prior art and propose a high-toughness, moisture-resistant, low-halogen epoxy resin composition that maintains high rigidity and high heat resistance while possessing excellent toughness and low water absorption. This solves the technical problems of existing epoxy resin systems, such as high brittleness and poor impact resistance, insufficient moisture-resistant heat resistance and easy warping, and the fact that adding rubber to toughen it will reduce heat resistance and rigidity and easily produce appearance defects.
[0009] To achieve the above objectives, the present invention provides the following technical solution:
[0010] A high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition comprising the following raw materials in parts by weight:
[0011] Epoxy resin: 100 parts by weight;
[0012] Hardener: 40-90 parts by weight;
[0013] Accelerator: 0.1-2.0 parts by weight.
[0014] Preferably, the curing agent is selected from biphenyl aralkyl novolac, naphthene novolac, or a combination thereof. The structural feature of biphenyl aralkyl novolac is that its main molecular chain contains rigid biphenyl groups, which are connected by flexible methylene bridges (-CH2-) or aralkyl segments.
[0015] The structural characteristics of naphthol phenolic resin are: the molecule contains naphthalene rings with a fused ring structure, and the naphthalene rings are also connected by methylene bridge bonds.
[0016] Both of these hardeners possess a relatively rigid aromatic planar structure, which imparts excellent heat resistance and rigidity to the cured material. Simultaneously, the presence of methylene bridging bonds provides moderate molecular chain flexibility, effectively dispersing impact energy, thus achieving a toughening effect that combines rigidity and flexibility. Furthermore, both biphenyl and naphthalene rings are highly hydrophobic, and their rigid molecular chains are easily packed tightly together, resulting in a small free volume after curing, making it difficult for water molecules to penetrate, thereby giving the material extremely low water absorption.
[0017] Preferably, the epoxy resin is selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, o-cresol formaldehyde epoxy resin, or mixtures thereof. To balance good wettability to carbon fiber / glass fiber and heat resistance of the cured product, the epoxy equivalent of the epoxy resin is 150-300 g / eq. Too low an epoxy equivalent (<150 g / eq) will result in excessive crosslinking and decreased toughness; too high an epoxy equivalent (>300 g / eq) will result in insufficient crosslinking density, reduced heat resistance, and decreased rigidity.
[0018] In addition, to further optimize micro-toughness, CTBN or core-shell rubber toughening epoxy resin may optionally be added to the composition.
[0019] Preferably, the accelerator is an organic urea accelerator (such as UR-300) or an imidazole accelerator (such as 2-methylimidazole, 2-ethyl-4-methylimidazole). The accelerator is used to regulate the reaction rate between the epoxy resin and the hardener to obtain suitable prepreg storage stability and processing window.
[0020] To further adjust the rheological properties of the resin composition, reduce curing shrinkage, or increase surface hardness, 0-30 parts by weight of inorganic filler may be selectively added.
[0021] Preferably, the inorganic filler is nano-silica, with an average particle size preferably of 10–100 nm. The addition of nano-silica can also improve the scratch resistance of the composite material to a certain extent.
[0022] This invention also provides a method for preparing a high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition, comprising the following steps:
[0023] 1) Add epoxy resin to a reactor equipped with heating and stirring devices, heat to 80-120°C and stir for 1-4 hours to completely melt and mix it evenly;
[0024] 2) Add the hardener to the reactor and continue stirring at 80-120°C for 1 hour to ensure that the hardener is completely melted and thoroughly mixed with the epoxy resin. Then, cool the reactor to 70°C and maintain equilibrium.
[0025] 3) Mix the accelerator with a small amount of liquid bisphenol A or bisphenol F epoxy resin evenly, and grind it with a three-roll mill until there are no particles. During this process, strictly control the temperature not to exceed 50°C to prevent the accelerator from reacting and becoming ineffective prematurely.
[0026] 4) When the temperature inside the reactor stabilizes at 70℃, add the accelerator mixture ground in step 3) into the reactor and stir for 10-15 minutes until homogeneous;
[0027] 5) After stirring, unload the resin composition from the reactor, bag it, and immediately freeze it to obtain the epoxy resin composition.
[0028] If the formula contains inorganic fillers, add the inorganic fillers and accelerators together to a small amount of epoxy resin, grind and disperse them together, and then put them into the reaction vessel.
[0029] Compared with the prior art, the present invention provides a high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition, which has the following beneficial effects:
[0030] (1) Excellent impact resistance and crack prevention performance: The present invention uses a biphenyl aryl or naphthol skeleton hardener with an intrinsic toughening structure. The epoxy resin composition prepared has extremely high notched impact strength after curing. The electronic product shell made of the composite material of the present invention will have a significantly improved pass rate in the ball impact test or the whole machine drop test, and can effectively prevent back panel cracking or cracking caused by accidental drop.
[0031] (2) Extremely low water absorption rate: The water absorption rate of the composition of the present invention can be controlled below 0.25%, which is far superior to the 0.5%-0.8% of the traditional system. This significantly reduces the risk of warping and deformation of the thin-walled back plate due to water absorption and expansion in a humid environment, and ensures the long-term dimensional stability of the product.
[0032] (3) High rigidity and high heat resistance: The composition of the present invention does not sacrifice rigidity and heat resistance while toughening. The flexural modulus can reach more than 125 GPa and the glass transition temperature (Tg) can reach more than 160℃, which meets the structural support requirements of thin-walled electronic products.
[0033] (4) Low halogen and environmentally friendly advantages: The biphenyl aryl phenolic resin and naphthol phenolic resin selected in this invention do not contain halogen atoms. At the same time, no halogen-containing flame retardant is actively added to the composition formulation, which can effectively dilute the halogen content in the epoxy resin, so that the total halogen concentration of the final formulation is reduced to below 500 ppm, which meets the stringent compliance requirements of electronic and electrical products for environmental protection and flame retardant materials.
[0034] (5) Excellent appearance quality: Since it does not rely on rubber elastomers as toughening agents, the present invention avoids appearance defects caused by the difference in refractive index between rubber and matrix resin. The cured composite material has a smooth, bright surface, no flow lines, and no white spots, which fully meets the stringent requirements of electronic product appearance parts for surface texture. Detailed Implementation
[0035] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0036] I. Raw Material Sources and Specifications
[0037] The raw material information used in the following examples and comparative examples is as follows, but is not limited to these sources:
[0038] Epoxy resin (bisphenol A type): epoxy equivalent approximately 185 g / eq, trade name EPON 828 (Hexion) or equivalent.
[0039] Hardener B1 (biphenyl aryl phenolic resin): Trademark name MEH-7851-3S (Meiwa Kasei) or equivalent product.
[0040] Hardener B2 (naphthol phenolic resin): Trademark name EXB-9500 (DIC Company) or equivalent product.
[0041] Hardener C1 (ordinary linear phenolic resin): Used in proportion.
[0042] Hardener C2 (DICY): Use in proportion.
[0043] Accelerators: Imidazoles, such as 2-methylimidazole.
[0044] Reinforcing material: Carbon fiber, Zhongfu Shenying SYT45 3K plain weave fabric, surface density 200 g / m² 2 .
[0045] Inorganic filler (optional): Nano-silica, average particle size 20 nm.
[0046] II. Preparation of Epoxy Resin Compositions
[0047] Example 1:
[0048] According to the formulation shown in Table 1, 100 parts by weight of bisphenol A epoxy resin were added to a reactor, heated to 100°C, and stirred for 2 hours until homogeneous. Then, 85 parts by weight of hardener B1 (biphenyl arylphenol resin) were added, and stirring was continued at 100°C for 1 hour until completely dissolved and homogeneous. The reactor was then cooled to 70°C. 0.5 parts by weight of 2-methylimidazole were mixed with 5 parts by weight of bisphenol A epoxy resin and milled three times with a three-roll mill until no particles were felt (temperature controlled ≤50°C). When the temperature inside the reactor stabilized at 70°C, the milled accelerator mixture was added to the reactor and stirred for 12 minutes until homogeneous. The mixture was unloaded, bagged, and immediately frozen at -20°C to obtain the epoxy resin composition of Example 1.
[0049] Example 2
[0050] The difference from Example 1 is that 90 parts by weight of hardener B2 (naphthol phenolic resin) is used instead of hardener B1, while the rest of the steps are exactly the same.
[0051] Comparative Example 1 (Ordinary Phenolic System)
[0052] The difference from Example 1 is that 50 parts by weight of hardener C1 (ordinary linear phenolic resin) is used instead of hardener B1, while the other steps are the same.
[0053] Comparative Example 2 (DICY System)
[0054] 100 parts by weight of bisphenol A epoxy resin were added to a reactor and heated to 100°C with stirring for 1 hour. 4 parts by weight of hardener C2 (DICY) and 0.5 parts by weight of 2-methylimidazole were mixed with 5 parts by weight of epoxy resin, ground evenly using a three-roll mill, and then added to the reactor. The mixture was stirred at 70°C for 10 minutes until homogeneous. The remaining steps were the same as in Example 1.
[0055] III. Preparation of Prepregs and Composite Boards
[0056] The epoxy resin compositions prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were removed from the freezer and melted at 70°C. The molten resin was then uniformly coated onto release paper using a roller coater to produce a product with a unit area weight of 75 g / m². 2 The adhesive film.
[0057] The carbon fiber cloth (SYT45 3K) is laid flat and arranged neatly, covered with a layer of adhesive film on the top and bottom, and briefly pressed with a hot roller at 100°C to allow the resin to fully impregnate the fiber. Then it is quickly cooled and wound up to obtain the prepreg. The resin content (RC) of the prepreg is controlled at 45%.
[0058] The above prepreg is laid in 12 layers with the same fiber direction, placed in a hot press mold, and hot-pressed and cured at 150°C and 1 MPa pressure for 30 minutes to obtain a composite material board with a thickness of about 1 mm. The board is then cut into various standard test strips using a CNC cutting machine.
[0059] IV. Performance Testing Methods
[0060] All tests were conducted in a standard laboratory environment (23℃±2℃, 50%±10% RH) and strictly in accordance with Chinese national standards (GB / T):
[0061] Glass transition temperature (Tg): Dynamic thermomechanical analysis (DMA) was used, three-point bending mode, heating rate 5℃ / min, frequency 1 Hz, in accordance with GB / T 40396-2021, and Tg was taken as the peak temperature of the tanδ curve;
[0062] Flexural modulus: Tested according to GB / T 3356-2014, with a span-to-thickness ratio of 32:1 and a loading rate of 2 mm / min;
[0063] Notched impact strength (Izod): Tested according to GB / T 1843-2008, type A notch, pendulum energy 5.5J;
[0064] Water absorption rate: Tested using a pressure cooking test (PCT) at 121℃, 100% RH for 2 hours, according to GB / T 1034-2008. Water absorption rate = (mass after moisture absorption - dry mass) / dry mass × 100%;
[0065] Warpage: Tested according to GB / T 1034-2008. After the composite material board is treated under PCT conditions (121℃, 100% RH) for 2 hours, it is taken out and placed on a flat marble platform. The maximum warpage height of the four corners of the board is measured (unit: mm).
[0066] Appearance quality: Visually inspect the surface of the composite material sheet under a standard D65 light source to see if it is flat and glossy, and whether there are white spots, flow lines or fogging.
[0067] V. The formulation and performance test results are shown in Table 1:
[0068]
[0069] VI. Results Analysis:
[0070] 1) Toughness (impact resistance): As can be seen from Table 1, the notched impact strengths of Example 1 and Example 2 are 85 kJ / m. 2 and 80 kJ / m 2 Comparative Example 1 (ordinary phenolic resin) only had 55 kJ / m³. 2 Comparative Example 2 (DICY) is 65 kJ / m 2 The impact strength of the embodiments of the present invention is increased by approximately 45% to 55% compared to the comparative examples. This fully demonstrates that using a hardener with a biphenyl aryl or naphthol backbone can significantly improve the toughness of the epoxy resin matrix without adding rubber-based toughening agents. This means that electronic product casings made using the composite material of the present invention will have a significantly higher pass rate in drop ball impact tests or whole-machine drop tests, effectively preventing back panel cracking or bursting caused by accidental drops.
[0071] (2) Rigidity (flexural modulus): As is well known to those skilled in the art, traditional toughening methods (such as adding rubber) typically lead to a decrease in modulus. However, the flexural moduli of Examples 1 and 2 of the present invention are 125 GPa and 130 GPa, respectively, which not only do not decrease but are slightly higher than those of Comparative Example 1 (120 GPa) and Comparative Example 2 (115 GPa). This is because the biphenyl group and naphthalene ring themselves have high rigidity, and they act as a "rigid skeleton" in the molecular structure, compensating for the modulus loss caused by the methylene flexible segment, and even achieving an increase in modulus. For the design of thin-walled backplates with a thickness of less than 0.8 mm, a flexural modulus of more than 125 GPa is key to ensuring the structural resistance to deformation.
[0072] (3) Moisture and heat resistance and dimensional stability: The water absorption rates of Examples 1 and 2 were as low as 0.22% and 0.18%, respectively, while those of Comparative Example 1 were 0.55% and Comparative Example 2 were as high as 0.9%. This difference was directly reflected in the warpage test: the warpage of the embodiments of the present invention was less than 0.2 mm, while that of Comparative Example 1 was 0.8 mm and that of Comparative Example 2 was 1.5 mm. For actual electronic products, a warpage of 0.2 mm is within the allowable range of assembly tolerances, while a warpage of more than 0.8 mm will lead to assembly failure or poor appearance.
[0073] The low water absorption rate stems from two aspects: firstly, the high hydrophobicity of biphenyl and naphthalene rings; and secondly, the dense molecular chain packing and small free volume after curing. The high water absorption rate of the DICY system is due to the presence of polar urea groups in its cured product, which readily form hydrogen bonds with water molecules.
[0074] (4) Heat resistance: The Tg values of Examples 1 and 2 were 160℃ and 175℃, respectively, both significantly higher than the 135℃ of Comparative Example 2. For backplanes that need to withstand the heat generated by electronic components and subsequent high-temperature processes (such as reflow soldering), a Tg > 150℃ is a basic requirement. The DICY system of Comparative Example 2 has significantly insufficient heat resistance, posing a risk of high-temperature softening in practical applications.
[0075] (5) Appearance quality: The composite material sheets of Examples 1 and 2 have smooth and glossy surfaces without any appearance defects. Comparative Example 1 has a decent appearance but poor toughness; Comparative Example 2 is prone to white spots, which is due to the limited solubility of DICY in epoxy resin, which may cause the precipitation of tiny crystals during the curing process.
[0076] VII. Technical Principles:
[0077] The technical principles of this invention can be explained from the following three aspects:
[0078] (1) Toughening mechanism of “combining rigidity and flexibility”: In traditional high cross-linking density phenolic resins (such as phenolic resins), benzene rings are directly and densely connected through short methylene groups. After curing, the molecular chain segments are almost completely locked and cannot dissipate impact energy through chain segment movement. Therefore, the material exhibits strong brittleness.
[0079] The biphenyl aryl phenolic resin or naphthol phenolic resin selected in this invention, in addition to providing rigid and heat-resistant rigid aromatic groups (biphenyl or naphthalene rings), also intentionally incorporates methylene bridging bonds or aryl segments with moderate rotational freedom in its molecular structure. When the material is subjected to external impact, these flexible segments can undergo minor conformational changes, absorbing and dispersing the impact energy, thereby effectively inhibiting the initiation and propagation of cracks. This toughening occurs at the molecular level of the resin matrix and is considered "intrinsic toughening," requiring no second phase such as rubber elastomers, thus not sacrificing heat resistance or appearance quality.
[0080] (2) Molecular design with low water absorption: The water absorption rate of a material mainly depends on the content of polar groups in its chemical structure and the free volume fraction after curing. Both biphenyl rings and naphthalene rings are highly hydrophobic aromatic structures, containing little or no hydrophilic groups. At the same time, due to the good planarity and regularity of these rigid aromatic rings, the molecular chains can be tightly packed during curing to form a dense cross-linked network, significantly reducing the free volume. Water molecules, as small molecules, have difficulty penetrating into this dense structure.
[0081] Therefore, the epoxy resin composition of the present invention maintains an extremely low water absorption rate (≤0.25%) even under high temperature and high humidity (PCT) conditions, which is far lower than that of the traditional DICY system (above 0.8%) and the ordinary phenolic system (above 0.5%). The low water absorption rate directly eliminates the internal stress caused by moisture absorption and swelling, thereby solving the problem of backing board warping and deformation at its root.
[0082] (3) Maintenance of a high-rigidity skeleton: Biphenyl groups and naphthalene groups themselves have a higher rigidity modulus than monophenyl rings. Therefore, the use of these hardeners will not only not reduce the flexural modulus, but will also maintain the flexural modulus of the cured product at a high level (above 125 GPa) due to the introduction of rigid aromatic rings. This is crucial for thin-walled backing plates with a thickness of less than 0.8 mm, because only a sufficiently high modulus can ensure that the product does not undergo excessive bending deformation during normal use and drop.
[0083] In summary, this invention has successfully developed a high-toughness, moisture-heat resistant, and low-halogen epoxy resin composition by selecting biphenyl aryl phenolic resin or naphthol phenolic resin as the curing agent for the epoxy resin. This composition significantly improves impact strength without sacrificing rigidity and heat resistance, while reducing water absorption to 1 / 3 to 1 / 5 of that of traditional systems, effectively solving the problem of moisture-induced warping. Its preparation process is simple, compatible with existing prepreg production lines, and produces an excellent appearance after curing. It is highly suitable for manufacturing thin and light back panels or structural components for high-end electronic products such as laptops, tablets, and mobile phones, and has broad application prospects.
[0084] The above description is merely a preferred embodiment of the present invention; however, the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and its improved concepts, should be covered within the scope of protection of the present invention.
Claims
1. A high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition, characterized in that, Including the following raw materials by weight: Epoxy resin: 100 parts by weight; Hardener: 40-90 parts by weight; Accelerator: 0.1-2.0 parts by weight; The hardener is selected from biphenyl alkylphenol resin, naphthol phenol resin, or a combination thereof.
2. The high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition according to claim 1, characterized in that, The epoxy resin is selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, o-cresol epoxy resin or a mixture thereof, and the epoxy equivalent of the epoxy resin is 150-300 g / eq.
3. The high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition according to claim 1, characterized in that, The accelerator is an organic urea accelerator or an imidazole accelerator.
4. The high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition according to claim 1, characterized in that, The composition also includes 0-30 parts by weight of inorganic filler.
5. The high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition according to claim 4, characterized in that, The inorganic filler is nano-silica.
6. The high-toughness, moisture-resistant, heat-resistant, low-halogen epoxy resin composition according to claim 1, characterized in that, The composition also includes CTBN or a core-shell rubber-toughened epoxy resin.
7. A method for preparing a high-toughness, moisture-resistant, low-halogen epoxy resin composition according to any one of claims 1 to 6, characterized in that, Includes the following steps: 1) Add epoxy resin to the reactor, heat to 80-120℃ and stir for 1-4 hours to make it melt evenly; 2) Add the hardener to the reactor and continue stirring at 80-120°C for 1 hour until it melts evenly, then cool it down to 70°C to equilibrate; 3) Mix the accelerator with a small amount of epoxy resin evenly, and grind it with a three-roll mill until there are no particles, while controlling the temperature not to exceed 50℃; 4) When the temperature inside the reactor drops to 70°C, add the ground accelerator mixture into the reactor and stir for 10-15 minutes until homogeneous; 5) After stirring, unload the resin composition from the reactor, bag it, and immediately freeze it to obtain the epoxy resin composition.
8. The method for preparing a high-toughness, moisture-resistant, low-halogen epoxy resin composition according to claim 7, characterized in that, When the composition contains inorganic fillers, they are added together with the accelerator and ground in step 3).
